Supercritical water oxidation of dyeing sludge. Issue 5 (February 2019) - Li, Jianna; Wang, Shuzhong; Jiang, Zhuohang; Yang, Chuang; Xu, Haitao
Abstract: Supercritical water oxidation (SCWO) of dyeing sludge has been conducted in a batch reactor, and experiments were investigated at reaction temperature of 520∼600 °C, oxidation coefficient of 1∼1.2, residence time of 120∼600 s and a fixed pressure of 25 MPa. Experimental results indicated that most of the organic matters were degraded at 600 °C, 25 MPa, oxidation coefficient of 1.2 within residence time of 600 s, which reached up to 99.80% of COD removal efficiency. Reaction temperature, oxidation coefficient and residence time all play significant influences on the removal of organic matters, and the reaction temperature is the most influential factor while oxidation coefficient and residence time become less significant as they exceed fixed values. Moreover, the effects of different catalysts on the degradation of organic matters were further studied to enhance the removal efficiency of COD and NH3 -N. It is suggested that all the tested catalysts (MnO2, CeO2, Al2 O3, ZrO2 ) could degrade COD and NH3 -N to a certain extent, but CeO2 has the highest activity compared with other catalysts.